UPAYA MENINGKATKAN HIDUP SEHAT MELALUI EFEKTIVITAS PEMBERDAYAAN USAHA KESEHATAN SEKOLAH - Sigit Raharjo; Rahmat Hermawan; Frans Nuseto (JUPE (Jurnal Penjaskesrek), 2014)
The objective of this research is empowering UKS effectively in SD N 1 Gutter Bojong. The method used is descriptive qualitative method, by taking a sample of grade IV, V and VI of SD Negeri 1 Gutter Bojong totaling 83 students. The results of this study are: the study include an overview of the state of SD 1 gutter Bojong Students are referred to in this study consisted of parental education, socioeconomic circumstances, and the mental state of students in the school have the course of the research students of SD Negeri 1 Gutter Bojong have physical state of the nutritional status in either category, frequency calculations, and the average percentage of respondents indicate that as many as 72 students or 86.43 % gave a good answer. The conclusion of this study is the implementation of the School Health Unit by UKS Officer of Health Service designated health center has been operating effectively in improving the health of studentsTujuan penelitian ini adalah untuk mewujudkan pemberdayan usaha kesehatan sekolah secara efektif di SD N 1 Talang Bojong. Metode yang di gunakan adalah metode penelitian deskriptif kualitatif . Hasil penelitian ini adalah penelitian ini meliputi gambaran mengenai keadaan Siswa SD 1 talang bojong yang dimaksud dalam penelitian ini terdiri dari pendidikan orang tua,keadaan sosial ekonomi, dan keadaan mental siswa dalam mengikuti pelajaran di sekolah dari penelitian ini siswa SD Negeri 1 Talang Bojong memiliki keadaan fisik dengan status gizi yang masuk dalam kategori baik rata-rata jawaban responden menunjukkan bahwa sebanyak 72 siswa atau 86,43% memberikan jawaban baik. Kesimpulan Pelaksanaan Usaha Kesehatan Sekolah oleh Petugas UKS dari Dinas Kesehatan yang ditunjuk Puskesmas sudah berjalan secara efektif dalam meningkatkan kesehatan siswa.Kata kunci : efektivitas UKS, kesehatan, pola hidup sehat